Human Error and Management in Gynecological and Obstetric Cases - Michail Michailidou, Evangelia; Skoura, Rafailia; Daniilidis, Angelos; Kalogiannidis, Ioannis; Eskitzis, Panagiotis (Clinical Medicine And Health Research Journal, 2023)
In this review we have collected information about errors that occur in gynecological and obstetric cases. Mistakes are an integral part of every sector, but our task should be to recognize and report mistakes. This will prevent problems that may appear later. Organizations promote health professionals in announcing their mistake to the person’s family but also to the person herself. Various error cases are described demonstrating the variety of errors that exist. In this way, health professionals and other people, possibly future patients, should understand that error is part of everyday life. Finally, health tips are suggested.